Circulating biomarkers of cardiovascular disease are related to aneurysm volume in abdominal aortic aneurysm - Bouwens, Elke (2023)
Funding Information: The authors disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This work is supported by Stichting Lijf en Leven. The sponsor had no role in study design, methods, subject recruitment, data collection or analysis, or preparation of the manuscript. Publisher Copyright: © The Author(s) 2023.